Too Great a Burden to Bear: The Struggle and Failure of the Freedmen’s Bureau in Texas - Rothera, Evan (Relations industrielles / Industrial Relations, 2017)
The article reviews the book, "Too Great a Burden to Bear: The Struggle and Failure of the Freedmen’s Bureau in Texas," by Christopher B. Bean.